Keruntuhan akhlak di kalangan budak-budak perempuan / Samsiah Abdullah - Samsiah, Abdullah (1977)
This study is to fulfill the lack of academic research on social problems faced by our country. The study focused on female deliquents with the intension to analyse the variables which are responsible for the dismoral behavior. Also the study is to see the relation between the problem faced by the deliquents and the different forms of deviant behavior done. The study contain 4 chapters. The 1st chapter is the introductory chapter, that is a brief discussion about the problem itself and the background of the research. The 2nd chapter analysed the variables and the role they played in affecting the dismoral behavior. The 3rd chapter discussed the relation between the problem faced by the female deliquents and the different types of offencesthey had done. In the concluding chapter is the summary of what had been founded based on the data discussed in the 2nd 3rd chapter. This chapter also include the role played by Rehabilitation Centers in re adjusting the inmates in the society.